HUBUNGAN SELF-ESTEEM DENGAN FEAR OF MISSING OUT (FOMO) PADA MAHASISWA - Nompo, Rifki Sakinah; Darista, Natalia Glory; Simon, Merlis; Fatimah, Fatimah; Fitriani, Fitriani (Juru Rawat. Jurnal Update Keperawatan, 2025)
Fear of Missing Out (FoMO) is a psychological phenomenon commonly experienced by university students in the digital era, characterized by anxiety arising from the perception of being excluded from others’ social activities. One of the factors influencing the emergence of FoMO is self-esteem. This study aims to examine the relationship between self-esteem and FoMO among college students. This research used a quantitative method with a correlational design using a cross-sectional approach. The sampling technique used was simple random sampling, resulting in a total of 90 student respondents. The study was conducted from July to August 2025. Data were collected using self-esteem and FoMO questionnaires and analyzed using the Spearman correlation test. The results indicate a significant relationship between self-esteem and FoMO among students, with a correlation coefficient of 0.238 and a significance value (p-value) of 0.024 (p < 0.05). The positive direction of the relationship suggests that the higher the self-esteem, the lower the level of FoMO. However, the strength of the association falls within the weak category. In conclusion, there is a significant yet weak relationship between self-esteem and FoMO among the students. The researcher recommends that a student support and counseling unit to help monitor and improve students’ mental well-being.